The Industrial Ergonomics Approach Influences Workforce Fatigue and Health and Increases Productivity - Gempur Santoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
Work should remain safe, comfortable and not tiring, but should result in good work results or good productivity. To achieve this, we need an ergonomic approach in industry so that work is not tiring and productivity increases. In this paper it is planned in a descriptive manner. Data is taken from various opinions in literature or called literature studies. Analysis was also carried out descriptively. Conclusion, Equipment adapted to the user's anthropometry will make the work posture and work range better, and work without bending over, so that work does not get tired quickly. The physical environment of the floor and ventilation that meet the requirements will be free from the occurrence of dizziness and headaches for workers; environment many biological microorganisms especially bacteria, fungi and viruses some occupations are particularly susceptible to contracting pneumonia while carrying out work duties; chemical environment exposure to polluting gases in the form of NOx, Sox, HC, and greenhouse gas particles will affect the health of workers such as damaging blood hemoglobin composition, upper respiratory tract infections, throat irritation, pneumococcal disease, cardiovascular disease and cancer, and exposure to benzene has an effect on hemoglobin and erythrocyte abnormalities. Therefore, if the industrial environment is healthy, the workforce will also be healthy